The Oculomotor Systems Ability to Adapt to Structural Changes Caused by the Process of Senescence: A Review - Bruenech, Jan Richard; Kjellevold Haugen, Inga-Britt; Bak, Ulla; Maagaard, Marianne; VanderWerf, Frans (Scandinavian Journal of Optometry and Visual Science, 2012)
Age-related binocular vision anomalies are frequently encountered during clinical examination of mature patients. Observations of both concomitant and incomitant restrictions in eye motility indicate that all oculomotor system levels are implicated, from cortical neurons down to extraocular muscles. The system can make adaptations in response to changes induced by growth and ageing, which it does by monitoring and adjusting its own performance. This adaptive mechanism, which is important for maintaining motility, spatial orientation, and perceptual stability, seems to rely on extra-retinal information about eye position in relation to the head and trunk. Receptors in the extraocular muscles and the vestibular system, assumed to contribute to this type of information, also undergo age-related changes. This may compromise their ability to assist in the adaptive process and in potential calibrations of other neural systems. Furthermore, recent observations of a dual, common, final pathway and double insertions of distal extraocular muscles suggest that muscle and tendon receptors may facilitate other, still unresolved, functions in the visual system. Consequently, age-related changes in certain mechanoreceptors may have more severe implications for ocular motility and visual functions than previously assumed. This review aims to detail some of the most frequent neurogenic and myogenic age-related changes that take place in the human oculomotor system and relevant pre-motor structures. It will also address clinical implications of these changes and the potential adaptive mechanism they initiate.